Analisis Perilaku Keuangan Masyarakat Dalamkonteks Pinjaman Rentenir: Perspektif Ekonomi Syariah - Kholidah, Nur; Rosanti, Cholisa; Hudaya, Fadli (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2024)
This study was conducted to gain a deeper understanding and analyze the factors that influence the community's borrowing behavior. It is hoped that in the future, the community will shift away from loan sharks and prefer existing banks, especially Islamic banks. The research methods used include direct interviews and the distribution of questionnaires to the villagers where the study was conducted. The sampling procedure in this study is the snowball sampling method with 68 respondents. The data analysis technique used is multiple regression analysis using SPSS version 2.2 The results of the study indicate that, simultaneously, the community's borrowing behavior is significantly influenced by Islamic financial literacy, needs, convenience, and collateral, as supported by the F-test result of 9.867. Meanwhile, partially, the factors of Islamic financial literacy and collateral have a significant negative influence on the community's borrowing behavior from loan sharks. The factor of needs has a significant positive influence on the community's borrowing behavior from loan sharks. The factor of convenience does not influence the community's borrowing behavior from loan sharks. REFERENSI Aziz, A., & Ramdansyah, R. (2016). Esensi Utang Dalam Konsep Ekonomi Islam. BISNIS: Jurnal Bisnis Dan Manajemen Islam, 4(1), 124–135. Bawono, A. (2006). Multivariate analysis dengan SPSS. Salatiga: STAIN salatiga press. Ediwijoyo, S. P., & Saefudin, S. A. (2021). Tingkat Religiusitas Dan Faktor Kebutuhan Terhadap Keputusan Pembiayaan Rentenir (Studi Pada Pedagang Pasar Wonokriyo Gombong). Jurnal E-Bis, 5(2), 514–529. Fielnanda, R., & Sahara, N. (2018). Pola Konsumsi Rumah Tangga Nelayan Di Desa Mendahara Ilir Kec. Mendahara Kabupaten Tanjung Jabung Timur. ILTIZAM Journal of Shariah Economics Research, 2(2), 89–107. Jalil, A. (2020). Hukum Perjanjian Islam: Kajian Teori dan Implimentasinya di Indonesia. CENDEKIA: Jurnal Studi Keislaman, 6(2), 214–233. Musadad, A. (2019). Konsep Hutang-Piutang Dalam Al-Qur’an. Dinar: Jurnal Ekonomi Dan Keuangan Islam, 6(1), 54–78. Novida, I., & Dahlan, D. (2020). Faktor-Faktor Yang Mempengaruhi Masyarakat Berhubungan Dengan Rentenir. AGHNIYA: Jurnal Ekonomi Islam, 2(2), 181–202. Pratama, A. R. P., & Wardhana, A. (2022). Pengaruh Kemudahan Penggunaan Aplikasi dan Promosi terhadap Keputusan Pembelian pada E-Commerce Shopee. YUME: Journal of Management, 5(2), 138–146. Shohib, M. (2015). Sikap terhadap uang dan perilaku berhutang. Jurnal Ilmiah Psikologi Terapan, 3(1), 132–143. Statistik, B. P. (2021). Berita resmi statistik. Bps. Go. Id, 27, 1–52. Yuswalina, Y. (2013). Hutang-Piutang dalam Prespektif Fiqh Muamalah di Desa Ujung Tanjung Kecamatan Banyuasin III Kabupaten Banyuasin. Intizar, 19(2), 395–410.